2019
DOI: 10.1038/s41598-019-54522-2
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of heart proteome changes in a diet-induced obesity model

Abstract: Obesity is a pandemic associated with a high incidence of cardiovascular disease; however, the mechanisms are not fully elucidated. Proteomics may provide a more in-depth understanding of the pathophysiological mechanisms and contribute to the identification of potential therapeutic targets. Thus, our study evaluated myocardial protein expression in healthy and obese rats, employing two proteomic approaches. Male Wistar rats were established in two groups (n = 13/group): control diet and Western diet fed for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 85 publications
6
19
1
2
Order By: Relevance
“…Additionally, excess dietary linoleic acid (LA) has also been related to increased collagen deposition in the left ventricle in C57BL/6 mice [ 16 ]. Collectively, our data may provide further evidence that high calorie intake triggers metabolic disorders, contributing to cardiac structure and function disorders [ 26 ]. The above-mentioned changes were also accompanied by cardiac protein expression alterations, including those related to cardiomyocyte contractility [ 27 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Additionally, excess dietary linoleic acid (LA) has also been related to increased collagen deposition in the left ventricle in C57BL/6 mice [ 16 ]. Collectively, our data may provide further evidence that high calorie intake triggers metabolic disorders, contributing to cardiac structure and function disorders [ 26 ]. The above-mentioned changes were also accompanied by cardiac protein expression alterations, including those related to cardiomyocyte contractility [ 27 ].…”
Section: Discussionmentioning
confidence: 80%
“…One of the metabolic consequences of dietary FA overload is increased activity of intracellular enzymes responsible for metabolization of these energetic substrates. Peroxisomal and mitochondrial β-oxidation are the major degradation pathways in fatty acid metabolism [ 26 , 49 ]. A recent study of Sikder et al (2018) showed an increased rate of FA β-oxidation in the hearts of mice subjected to diet-induced obesity [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of some previous studies, where non-targeted proteomic methods were applied for the screening of cardiac tissue in animal model of dietary induced obesity, are mostly consistent with our observations. A map of the cardiac proteome in obese rats showed that the proteins involved in regulation of metabolism were predominantly changed [44]. The proteomic machinery responsible for fatty acids uptake and oxidation was upregulated in obese animals without hypertrophied hearts [44].…”
Section: Morphological and Molecular Characteristics Of The Heart In mentioning
confidence: 99%
“…A map of the cardiac proteome in obese rats showed that the proteins involved in regulation of metabolism were predominantly changed [44]. The proteomic machinery responsible for fatty acids uptake and oxidation was upregulated in obese animals without hypertrophied hearts [44].…”
Section: Morphological and Molecular Characteristics Of The Heart In mentioning
confidence: 99%
“…The CD was custom-formulated with the same ingredients as the WDF and WDS except for fructose, sucrose, palm oil, and lard added only in the WDF and WDS, and soybean oil added only in the CD to produce three different diets in fat, protein, and carbohydrate contents (Table 1 and Figure 2). The CD and WDF have been used in our previous study [18]. .…”
Section: Diet Compositionmentioning
confidence: 99%